Feasibility Study on Application of Various MADM Approaches for Selection of Kenaf/Saw Dust Composite - Vishwas Mahesh (Mechanics of Advanced Composite Structures)
This study focuses on the mechanical characterization and application of the various Multiple Attribute Decision Making (MADM) approaches for the selection of composites fabricated using two natural fibers, kenaf, and sawdust. Mechanical characterization involves testing the physical properties of these materials, such as tensile strength, flexural strength, and impact strength along with density and water absorption, to determine their mechanical behavior and suitability for various applications. The MADM approaches namely VIKOR and PSI are used to evaluate the mechanical properties of kenaf and sawdust reinforced composites for different applications based on multiple criteria or attributes. The study analyzes the trade-offs between different attributes to identify the optimal composite configuration for a given application. MADM technique offers a helpful framework for assessing the mechanical attributes of fiber-reinforced composites thereby determining their possible uses in a variety of sectors. However, it is essential to use the MADM approach in conjunction with other methods of material characterization and testing to ensure that the final decision is based on a comprehensive understanding of the material's properties and performance. The outcomes of this feasibility study will benefit researchers, manufacturers, and decision-makers involved in the selection and development of composite materials. It can assist in optimizing the material selection process, promoting sustainable and environmentally friendly choices, and enhancing the overall performance and cost-effectiveness of composite materials in various applications.